An assessment of geomorphic evolution and some erosion affected areas of Digha-Sankarpur coastal tract, West Bengal, India - Kamila, Amrit; Bandyopadhyay, Jatisankar; Paul, Ashis Kumar (Journal of coastal conservation, 2020)
The coastal sites of Ramnagar-I and Ramnagar-II Administrative Blocks (Kanthi Coastal Plain), Purba Medinipur District, West Bengal, India, reveal various morphological features, which are represented by four categories of surface formation under different processes in the present study through a contour plan with 50 cm contour interval. The first category of landform being some isolated ridges with above 10 m elevation, which are stretched out in a linear pattern parallel to the modern shoreline behind Ramnagar-Deuli beach ridge section. The second set of landforms of the area which ranges from 7 m to 10 m elevation from the MSL is extended in the form of sandy terrace and continuous sand ridge surface along the sides of the first category landform. The third category of landform is visible along the edges of the second category of continuous sand ridge topography in the form of an extensive sandy tract with the reactivated sand surface. Last category of the ancient surface with an elevation of 2.5 m to 5.0 m above MSL is also clearly visible from the wide valley flat surface depressions in between the Contai-Paniparul beach ridge section and Ramnagar-Deuli beach ridge section at present. Some crenulated ridges of sandy sediments observed in the the present contour plan, particularly along the bank of abandoned channels. These are most probably evolved in the ancient period by natural levee depositions from various fluvio-tidal channels of the coastal plain. They are also categorized into older natural levees and younger natural levees delineated from the tonal contrasts of images and field verification of lose sediments. The older natural levees represent oxidized soils and the younger one represents the grey white color of sediments. Tidal prisms are the result of spring time tidal waves, keeping pressure on the seaward sides and spill over the backshore area by entering into the tidal channels at the time of high tide in the coastal belt. The study reveal the effects of significant increase of tidal prism estimated from 1990 to 2017.